2007
DOI: 10.1093/cvr/cvm047
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional regulation of Ca2+ sparks by mitochondria-derived reactive oxygen species in cardiac myocytes

Abstract: Mitochondrial ROS exert bidirectional regulation of Ca(2+) sparks in a dose- and time (history)-dependent manner, and basal ROS constitute a hitherto unappreciated determinant for the production of spontaneous Ca(2+) sparks. As such, ROS signalling may play an important role in Ca(2+) homeostasis as well as Ca(2+) dysregulation in oxidative stress-related diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
108
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(115 citation statements)
references
References 31 publications
4
108
0
3
Order By: Relevance
“…The FFA present in cells provides a perpetuating and propagating mechanism for oxidative stress via the process of lipid peroxidation and produces large amounts of ROS and free radicals that cause secondary damage to cellular membranes and key organelles, including the ER; additionally, the SERCAs in the membrane of the ER are highly sensitive to ROS (6,52). In our study, we observed distinct alterations in the cytosolic calcium homeostasis after the exposure of the hepatocytes to PA (Fig.…”
Section: Discussionsupporting
confidence: 50%
“…The FFA present in cells provides a perpetuating and propagating mechanism for oxidative stress via the process of lipid peroxidation and produces large amounts of ROS and free radicals that cause secondary damage to cellular membranes and key organelles, including the ER; additionally, the SERCAs in the membrane of the ER are highly sensitive to ROS (6,52). In our study, we observed distinct alterations in the cytosolic calcium homeostasis after the exposure of the hepatocytes to PA (Fig.…”
Section: Discussionsupporting
confidence: 50%
“…The RyR amino acid sequence immediately proximal to S2808 is RRIS, which implicates a PKA site and therefore a potentially important substrate for ā¤-adrenergic signaling. Such exposure would furthermore leave RyR function particularly susceptible to oxidative stress, which is known to liberate protein-bound zinc (9,34) and also to enhance RyR open probability (37).…”
Section: Discussionmentioning
confidence: 99%
“…Increases in mitochondrial Ca 2+ concentration ([Ca 2+ ] m ) induce the opening of the mitochondrial permeability transition pore (MPTP) leading to inhibition of ATP synthesis, increased ROS production, cytochrome c release and cell death by apoptosis (6,7). Ruthenium red (RR) and Ru360 block the MCU to reduce the Ca 2+ influx and, therefore, exert a beneficial effect during I/R injury by preventing Ca 2+ accumulation (8).…”
Section: Introductionmentioning
confidence: 99%